Cytogenetic analysis of B chromosomes in one population of the fish Moenkhausia sanctaefilomenae (Steindachner, 1907) (Teleostei, Characiformes) - Hashimoto, Diogo Teruo [UNESP]; Voltolin, Tatiana Aparecida [UNESP]; Valim de Arruda Paes, Ana Danyelle Noitel [UNESP]; Foresti, Fausto [UNESP]; Bortolozzi, Jehud [UNESP]; Porto-Foresti, Fábio [UNESP] (Zoological Inst, 2012)
The aim of this study was to characterize cytogenetically one population of the fish Moenkhausia sanctaefilomenae (Steindachner, 1907), with emphasis on the analysis of B chromosomes. The nucleolar activity in the B microchromosomes was characterized, and an analysis of mitotic instability of these microchromosomes was accomplished. The results showed a diploid chromosome number of 50 chromosomes. In all individuals, we observed the presence of B microchromosomes with intra- and inter-individual variability. The analysis of the nucleolus organizing regions (NORs) by silver nitrate staining demonstrated multiple NORs. We observed active sites of ribosomal DNA in the B microchromosomes, with a frequency of 20% in the analyzed cells, which shows gene activity in these chromosomal elements. The analysis of constitutive heterochromatin patterns showed that the B microchromosomes are heterochromatic or euchromatic, which demonstrates differentiation of DNA composition between these genomic elements. The calculation of the mitotic instability index implied that B chromosomes in this species might be in a final stage of instability.
Keywords: fish cytogenetic; NOR expression; supernumerary chromosomes; mitotic instability